2005
DOI: 10.1080/14622200412331328475
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an adolescent smoking consequences questionnaire

Abstract: Several researchers have investigated the role of outcome expectancies in the initiation and maintenance of smoking behavior. Empirical studies with adults, using a validated self-report instrument, have shown that smokers identify higher levels of positive smoking expectancies and lower levels of negative smoking expectancies compared with nonsmokers and ex-smokers. Studies examining smoking outcome expectancies among adolescents have yielded similar findings, but many of these studies did not use a self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 28 publications
4
69
2
Order By: Relevance
“…Indeed, a common expectation of both adult (Copeland, Brandon, & Quinn, 1995) and adolescent (Lewis-Esquerre, Rodrigue, & Kahler, 2005) smokers is that smoking somehow alleviates negative affect. Yet, studies examining the direct effects of smoking on negative affect have provided mixed results.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, a common expectation of both adult (Copeland, Brandon, & Quinn, 1995) and adolescent (Lewis-Esquerre, Rodrigue, & Kahler, 2005) smokers is that smoking somehow alleviates negative affect. Yet, studies examining the direct effects of smoking on negative affect have provided mixed results.…”
Section: Introductionmentioning
confidence: 98%
“…Since the SCQ was introduced, several versions have been developed and validated for use with specifi c populations ( Cepeda-Benito & Ferrer, 2000 ;Copeland et al, 1995 ;Lewis-Esquerre, Rodrigue, & Kahler, 2005 ;Myers, McCarthy, MacPherson, & Brown, 2003 ). The original SCQ was developed with college students ( Brandon & Baker ) and comprises four factors: Negative Conse quences, Positive Reinforcement-Sensory Satisfaction, Negative Reinforcement-Negative Affect Reduction, and Appetite-Weight Control.…”
Section: The Smoking Consequences Questionnairementioning
confidence: 99%
“…Several studies have demonstrated that smoking outcome expectancies predict smoking-related behaviors in both adults ( Brandon & Baker, 1991 ;Copeland, Brandon, & Quinn, 1995 ) and adolescents ( Anderson, Pollak, & Wetter, 2002 ;Hine, Honan, Marks, & Brettschneider, 2007 ;Lewis-Esquerre, Rodrigue, & Kahler, 2005 ;Wahl, Turner, Mermelstein, & Flay, 2005 ); however, there is a debate when it comes to identifying the number and content of outcome expectancy factors. Smoking outcome expectancies can be defi ned as beliefs about the possible effects associated with smoking on behavior, cognition, moods, and emotions.…”
Section: Introductionmentioning
confidence: 99%